Perbandingan Produktivitas Pancing Ulur (HandLine) Dan Jaring Insang (Gill net) Nelayan Desa Kusamba, Klungkung, Bali Terhadap Hasil Tangkapan Ikan Tongkol (Auxis sp.) - Aryasuta, Pande Chrisna; Dirgayusa, I Gusti Ngurah Putra; Puspitha, Ni Luh Putu Ria (Journal of Marine and Aquatic Sciences; Vol 6 No 2 (2020)DO - 10.24843/jmas.2020.v06.i02.p12, 2020)
This study uses two environmentally friendly fishing gears namely gill net and hand line . The length of one set of hand line is 100 m and the length of one set of gill net s is 250 m. The purpose of this study was to determine the number of catch es, species composition of catch es and the efficiency of fishing gear that provided benefits for the fishermen of Kusamba Village. This data collection was carried out in field plunge directly with fishermen using the one day trip method for 35 trip s during the tuna fishing season by Kusamba Village fishermen. Auxis sp is one type of fish that is the main target of the catch of fishermen in Kusamba Village. Auxis sp often follows the current circulation, the catch of Auxis sp on the fishermen of Kusamba Village has a different amount of production every day. In terms of Auxis sp catch es by Kusamba Village Fishermen who use two fishing gear are dominated by gill net s and the quality aspect is dominated by hand linecatch es. It is known that there are two types of tuna, namely Auxis rochei and Auxis thazard. The catch is in principle the output of fishing activities, while the effort needed in principle is an input from the fishing activities, fisheries production in an area has increased or decreased can be seen from the results of CPUE. The highest CPUE value of gill net s is 53.75 tails / effort , the highest CPUE value of hand line is 75 tails / effort .